Bezpieczeństwo społeczno-ekonomiczne Polski z perspektywy czynnika demograficznego - Rosłon-Żmuda, Joanna (Przegląd Strategiczny, 2013)
In the second half of the XX century, when intensity of coexistence in international relations increased and globalizing processes accelerated, security stopped being identified with political and military dimension only. Other spheres of state’s activity as: economy, ecology, culture or society, emerged to be as much important for national security as problems which appear in the mentioned spheres may threaten it. In Poland, disadvatageous demographic changes which are taking place in the society, are one of such problems. It is claimed that fatal effects will be observed in 20 years and they will be forming national security of the country, especially its economic and social aspect.